KEBIJAKAN PEMERINTAH BAGI PERLINDUNGAN DAN KESELAMATAN MASYARAKAT TERHADAP DAMPAK PANDEMI COVID 19 DI INDONESIA (Institut Pemerintahan Dalam Negeri, 2021)
This paper aims to get an overview of how far the Government’s policies are for the protection and safety of the community against the impact of the Covid 19 pandemic, which is currently endemic throughout the world, even in Indonesia. The transmission of covid 19 in Indonesia, for almost 10 months, has infected part of the population in Indonesia, especially in areas in almost all provinces, districts/ cities in Indonesia. The confirmed transmission rate up to the beginning of February 2021, has reached a number above 1 million positive people are confirmed positive, and those who died have reached over 30,000 people, and those who recovered have reached above 900,000 people. As a result of the increasing number of confirmed positives, the impact on the availability of treatment isolation rooms is already approaching the acceptable threshold according to WHO standards, the number of people who have died, resulting in the increasingly limited land for burials. The method used in this paper is to use aqualitative descriptive study method, by obtaining data from print media, electronic media and other literature related to government policies in handling Covid 19. The conclusion that is found is, the Government has carried out various policies in handling of covid 19, in particular with the stipulation of Perpu 1 of 2020, concerning State Financial Policy and State Financial System Stabilization (facing Covid 19) in Indonesia, with this policy providing social assistance for people affected by Covid 19. And providing assistance to MSMEs who affected by covid 19, as well as PPh 21 incentives for affected entrepreneurs, and providing assistance to people with salaries below 5 million each month. As well as providing basic food assistance to the wider community affected by Covid 19 in 2020 and continuing in the 2021 budget year, as a top priority.Keywords: Policy, Protection, Community Safety, Covid Pandemic 19